Solve for x (3x + 5)(2x - 6) = 0
Follow Math Help Forum on Facebook and Google+
If the product of factors equals zero, then at least one factor equals 0. You have 2 factors. Set them equal to zero and solve for x.
set each factor equal to 0 ... 3x + 5 = 0 x = -5/3 2x - 6 = 0 x = 3
Please Explain? Originally Posted by Chop Suey If the product of factors equals zero, then at least one factor equals 0. You have 2 factors. Set them equal to zero and solve for x.
Another problem! Solve for x 2x - 9 < 9x + 4 & -4x - 6 > 7x - 14
View Tag Cloud